Text Neck Syndrome And Smartphone Use Among Medical Students In Lahore (Journal of Rashid Latif Medical College, 2025)
Background: Extended smartphone use with continuous neck flexion has been associated with neck pain and musculoskeletal symptoms, which are referred to as Text Neck Syndrome (TNS).Objective: To estimate the prevalence of TNS in medical students in Lahore and to evaluate associations with smartphone use (daily duration and typical neck posture).Methodology: Cross-sectional survey of 320 medical students from two Lahore medical colleges asked for demographics, smartphone exposure (hours/day, years of use), usual neck posture, and symptoms related to TNS. TNS was considered as occurrence of ≥3 characteristic symptoms with smartphone use ≥4 hours/day. Data analysis was performed using descriptive statistics and chi-square tests (α = 0.05).Results: Total TNS prevalence was 61.9% (198/320). Prevalence was greater with daily smartphone use: ≤2 h (42.6%), 2–5 h (61.0%), >5 h (76.5%) (p < 0.001). More frequent neck flexion >30° was predictive of greater TNS prevalence (73.4%) compared with <15° (44.4%) (p = 0.02). These results are consistent with similar student populations and meta-analytic data associating smartphone overuse with neck pain.Conclusion: TNS is prevalent among medical students in Lahore and significantly related to increased daily smartphone use and unfavorable neck posture. Ergonomic training and behavioral therapy to decrease prolonged smartphone use and enhance neutral head posture are advised.